Exploring nursing students' experiences of a drop-in support-centre: A mixed-methods study. (October 2018) - Martin, Marian; Ramjan, Lucie M.; Everett, Bronwyn; Glew, Paul; Lynch, Joan; Salamonson, Yenna
Abstract: Background: The increased use of blended learning approaches in undergraduate nursing programs has resulted in reduced on-campus contact with academic staff and other students. Objectives: To explore student's experiences of a Drop-In-Support-Centre and assess the impact of attendance on academic performance. Design: Concurrent mixed-methods. Setting: A large metropolitan, multi-campus university in Sydney, Australia. Participants: Undergraduate nursing students enrolled in a 3-year Bachelor of Nursing program. Methods: In March 2016, to support students' learning, a weekly Drop-In-Support-Centre (DISC) initiative was piloted. The DISC provided an informal, learning space one day a week for students to access academic support. Baseline quantitative data was extracted from the University administrative dataset with a 12-month follow-up Grade Point Average (GPA) in January 2017. Attendance at the DISC was collected progressively throughout 2016. Qualitative data were collected using semi-structured interviews. Results: Of 1016 undergraduate nursing students enrolled on the campus, 163 (16%) attended DISC at least once. Attendees were older, more likely to be Overseas-born (74% versus 45% native-born, p < 0.001). Sub-group analysis of first year students revealed attendees had a higher grade point average than non-attendees (4.20 versus 3.85, p = 0.005). Controlling for demographic factors, they were over three times more likely (Adjusted Odds Ratio: 3.75, 95% CI: 1.44–9.78) to achieve a higher GPA (>4.0) compared to non-attendees. Thirteen students were interviewed. Two main themes emerged; 1) 'Home away from home' and 2) 'A sense of community: Everyone supports each other' with three accompanying sub-themes. Conclusions: This study supports the usefulness of a Drop-In-Support-Centre in enhancing students' learning experiences and outcomes. The success of the program is highlighted by an improvement in academic performance of students who attended the DISC.